System of optimization of formation of students’ capacity for independent life choices - Elina Aliieva (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This article presents the structure of the capacity for independent life choices, methods of diagnosis of this ability, and the results of the pilot study on formation of students’ capacity for independent life choices; examined how influence social and psychological factors on the formation of this ability; substantiated and proven effectiveness of the system optimize formation of students’ capacity for independent life choices.